Aberrant expression of microRNAs in peripheral blood mononuclear cells as candidate biomarkers in patients with axial spondyloarthritis. (16th April 2019) - Li, Xiaomin; Lv, Qing; Tu, Liudan; Zhao, Minjing; Zhang, Peizhuo; Li, Qiuxia; Wei, Qiujing; Cao, Shuangyan; Gu, Jieruo
Abstract: Objectives: Axial spondyloarthritis (axSpA) is a chronic inflammatory arthritis involving the axial skeleton. Recent evidence suggests that microRNAs (miRNAs) play a critical role in ankylosing spondylitis (AS). In this study, we aimed to investigate whether miR‐17‐5p, miR‐27a, miR‐29a and miR‐126‐3p can be verified as potential biomarkers of axSpA. Methods: Peripheral blood mononuclear cell (PBMC) miRNA expression was evaluated by quantitative real‐time polymerase chain reaction among 43 patients with AS, 26 patients with non‐radiographic axSpA (nr‐axSpA) and 39 healthy controls. Detailed clinical histories were recorded and the correlation of miRNAs and clinical features were analyzed. Results: When compared to controls, both patients with AS and nr‐axSpA had significantly higher expression levels of miR‐17‐5p, miR‐27a, miR‐29a and miR‐126‐3p. MiR‐27a was negatively correlated with Ankylosing Spondylitis Disease Activity Score as well as C‐reactive protein in patients with nr‐axSpA ( r  = −0.51, P  < 0.01 and r  = −0.42, P  = 0.034 respectively). No other clinical features were found to correlate with the four miRNAs in patients with AS. Mir‐29a showed highest area under the curve with 0.952 and these four miRNAs may be potential biomarkers in patients with axSpA. Conclusions: We reported elevated miR‐17‐5p, miR‐27a, miR‐29a and miR‐126‐3p expression in PBMCs of patients with axSpA, and the expression of these four miRNAs might be used as useful diagnostic markers in axSpA.